Volumetric and performance-based evaluation of bituminous blends / Lee Leon ... [et al.] - Lee, Leon; Maharaj, Chris; Ramoutar, Lisa; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2025)
Crumb rubber (CR) and styrene-butadiene-styrene (SBS) from discarded tires and other waste materials were used as additives/replacements in asphalt mixtures. The researchers conducted Marshall and performance-based crumb rubber-modified asphalt (CRMA) testing. The dry process was employed, where CR was added to the aggregate before adding the binder. A control of 0% CR was compared to 1% CR by aggregate weight. Mix design formulations were acceptable for 5.6% and 6.3% binder contents, respectively. Marshall test results were acceptable for both formulations. For performance-based testing, the tensile strength ratio was acceptable for both formulations. However, for permanent deformation strain, the 1% CRMA was slightly higher (5.1%) than the upper acceptable range limit (4.5%), whereas the 0% CRMA control was within the acceptable range. Further investigation into the pre-treatment of CR to facilitate swelling and the phase interlocking to decrease the required binder in the mix design and increase CR addition is warranted. This study demonstrated the potential of reusing CR in road paving applications, providing an innovative, sustainable disposal option.